A qualitative investigation to identify the perceived educational needs of qualified nurses needed to reduce the use of antipsychotic medication when caring for people with dementia in an adult care setting. - Sutton, Jennifer (2011)
Background: Literature shows that the main challenge of caring for people with dementia is managing difficult behaviour caused by the behavioural and psychological symptoms of dementia (BPSD). Poor knowledge and understanding of BPSD, due to a lack of education in both pre and post-registration nursing programs, has lead to the inappropriate use of antipsychotics which are known to have detrimental effects for people with dementia. This study aimed to identify the perceived educational needs of qualified nurses to reduce the use of antipsychotic medication when caring for people with dementia in an adult care setting.